فشاری دەروونی دایکان و پەیوەندی بە دڵەڕاوکێی دابڕان لای منداڵانی باخچەی ساوایان لە سەنتەری شاری سلێمانی - عبدالله, م. د.فرمان زاهر; سەنگاوی, م. د.هوشیار صدیق (Sulaimani Journal for Humanities, 2024)
Previous research has indicated that children of depressed mothers are at risk for developing mental health problems such as anxiety and depression. To our knowledge, no study has been conducted to examine mothers’ psychological stress and it is association with children’s separation anxiety in the center of Sulaymaniyah city. Therefore, the current study was conducted due to the importance of this issue. Data was collected from (120) mothers of kindergarten children, and the number of their children consisted of (52) male and (68) female. After extracting psychometric characteristics, the researchers used the Levenstein et al (1993) questionnaire to assess psychological stress and the parents' version of Mendezt et al (2014) to assess children's separation anxiety. Statistical tests such as Kolmogorov, Cronbach-alpha, t- test and Regression analysis were utilized in the present study. The results of the study showed that mothers suffer from a high level of psychological stress; nevertheless, their children's separation anxiety level was not statistically high. It was also found that there is a statistically significant relationship between mothers’ psychological stress and their children’s separation anxiety. No significant difference between gender was found in separation anxiety. In light of the results, certain recommendations have been made
Keywords: Psychological Stress; Anxiety; Separation Anxiety